Implementation of a low cost data acquisition board for photovoltaic arrays analysis and diagnostic - Sousa, Sérgio (2014)
Testing PV modules are one of the important procedures to ensure the conformity with the standards and quality of this equipment’s. To implement some of the PV modules tests a data acquisition system is required. This paper presents the design and implementation of a data acquisition system for photovoltaic systems. The developed system is characterized by a low cost board based on a microcontroller. The description of the hardware as well an application to test its performance is presented. The developed system can be used for reading, storing and analyzing information from several photovoltaic systems. Experimental tests are presented to confirm the characteristics of the developed data acquisition board.